PENINGKATAN KAWALAN BRITISH MELALUI PERJANJIAN PERLIS-BRITISH 1930 DAN PENGUKUHAN KUASA ELIT MELAYU - Abd Manaf, Azmah; Ahmad, Azwan (SEJARAH: Journal of the Department of History, 2017)
The existence of Perlis as a state in Peninsular Malaysia shows a long history involving foreign powers and influence of the Siamese and the British. Perlis was part of Kedah and the politics of foreign powers had put Perlis as a new sovereign state with its ruler known as Raja. For most of the Malay states, British protectorate demonstrated poor command of the sultan or the ruler of the authority and administration of their respective states. But for Perlis, though terms of the agreement were not significantly different, the Perlis government, under the British protection had a positive impact in strengthening the Malay elite’s power in the state administration. In creating a good relationship with the British, the Perlis’s Malay elite, administrators managed to limit the British influence in the state administration. On the other hand, the British seemed to agree with the decisions by the Perlis’s Malay elites in some occasions. This article also shows how the Islamic reformist movement influences the Perlis’s Malay elites administrators. They used the ideas of the movement to strengthen their position in the state and in the eyes of the Malay community.